Simulation of flow around a flapping wing using two-dimensional vortex method / Akhmad Farid Widodo, Lavi Rizki Zuhal and Hari Muhammad - Akhmad Farid Widodo; Lavi Rizki Zuhal; Hari Muhammad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2013)
In this work, two dimensional vortex method is developed and used to simulate flows around a flapping wing. The method solves Navier-Stokes equation in term of vorticity. The solving strategy is to split the equation into diffusion and convection terms, and solved them separately. The diffusion term is modelled by Particles Strength Exchange (PSE) which is the most accurate of diffusion modelling in vortex method. The convection term that represents transport of particles is calculated by time step integration of velocity. To exercise the capability of the method in handling complex flows, we carried out simulation of flow field around a flapping wing. The flapping cycle includes two strokes with rapid rotation near reversal stroke. The result demonstrates conformity of the simulation with experiment in revealing mechanism of force production due to wake capturing. The results also show spurious peaks of lift of simulation because of disappearance of vortex stretching.